Harnessing the Potential of Roots of Traditional Power Plant: Ocimum - Vibha Pandey; Ravi Kant Swami; Alka Narula (Frontiers in Plant Science, 2021)
Genus Ocimum of Labiatae is well known in all traditional medicinal systems like Ayurveda, Unani, Siddha, and Homeopathy. The pharmaceutical activities of different species of Ocimum attributed to all plant parts. Roots are the most significant vital organ of the plant, as they absorb water and nutrients from soil and transport to aerial parts of the plants. Roots of Ocimum were found helpful with free-radical scavenging activity to improve physical and mental strength as well as to treat diabetes, malaria, and liver problems. Antibacterial activity of Ocimum roots and its main component, rosmarinic acid, is very beneficial to protect against several human pathogens, including bacteria and viruses. Being so important in every way, roots of Ocimum need healthy rhizosphere. Bacteria, fungi, nematodes, types of soil, fungicide, pesticides, salt, radioactive elements, as well as heavy metal contaminations, affect roots and overall growth of Ocimum in positive or negative ways. Each component of rhizosphere (natural, treatment or contamination) affects the roots, which highlights current ecological scenario to discover biosafe and more productive approaches. For such prestigious organ of Ocimum, development of in vitro root cultures and hairy root cultures assists to reduce the efforts and timing of the traditional cultivation process along with elimination of negative factors in rhizosphere. Different strains of Agrobacterium rhizogenes, various media compositions, as well as discrete treatments, like elicitors, on nonidentical species or cultivars of Ocimum boost the root induction, biomass, and accumulation of phytoceuticals differently. Hairy roots and in vitro roots of Ocimum accumulate higher quantity of therapeutic metabolites. These metabolites include several phenolics (like rosmarinic acid, 3-hydroxybenzoic acid, m-coumaric acid, p-coumaric acid, caffeic acid, ferulic acid, vanillic acid, chicoric acid, and lithospermic acid), triterpenes (such as betulinic acid, 3-epimaslinic acid, alphitolic acid, euscaphic acids, oleanolic acid, and ursolic acid) as well as flavonoids (flavones, flavonols, and dihydroflavonols). This review highlights pharmaceutical applications of Ocimum roots, a great deal of rhizosphere components and in vitro culturing techniques to enhance biomass as well as chief phytoceuticals.